Equality of Rights in the Work of the Codification Commission of the Republic of Poland on Drafts of Matrimonial Property Law - Michał Glück (Journal on European History of Law)
The Codification Commission of the Republic of Poland was set up in 1919 to unify and codify the legal system. At the time, the legal systems of the partitioning states were in force in the Polish lands, which definitely hampered the work of the Commission. It applied to all branches of law, including matrimonial property law. The preparation of uniform provisions of matrimonial property law was not the only challenge for the Commission members drafting that section. The inter-war period was a time of many social changes in the context of equality in both Poland and Europe. In 1920, the Eighth Conference of the International Woman Suffrage Alliance, which adopted resolutions on the equality of matrimonial property regimes, was held in Geneva. As a result, the Codification Commission sought to unify the system of matrimonial property law and adapt it adequately to the changes occurring at the time. In 1920-1939, the work on draft matrimonial property law was carried out by two rapporteurs: W. L. Jaworski and K. Lutostański, who submitted in total four versions of the draft matrimonial property law. The deliberations of the Civil Law Section, subsequently the matrimonial property law sub-commission, over equality issues in draft laws frequently proceeded in a dynamic manner. This fact definitely had an impact on the work on the draft law and the adequate introduction of the value of gender egalitarianism to the prepared matrimonial property law. This article aims to show the work of the Commission on the draft laws, taking into account the context of equality and changes affecting the content of the prepared provisions.